Continued muscle loss increases mortality in cirrhosis: Impact of aetiology of liver disease. (26th January 2020) - Welch, Nicole; Dasarathy, Jaividhya; Runkana, Ashok; Penumatsa, Revathi; Bellar, Annette; Reen, Jaspreet; Rotroff, Daniel; McCullough, Arthur J.; Dasarathy, Srinivasan
Abstract: Background and Aims: Sarcopenia or skeletal muscle loss adversely affects outcomes in cirrhosis. The impact of aetiology of liver disease on the severity or the rate of muscle loss is not known. Methods: Consecutive, well‐characterized adult patients with cirrhosis due to viral hepatitis (VH), alcoholic liver disease (ALD) or non‐alcoholic fatty liver disease (NAFLD) and non‐diseased controls with at least two temporally distinct abdominal CT (computed tomography) scans were evaluated. Psoas, paraspinal and abdominal wall muscle areas at the L3 vertebra level were quantified on the CT scans. Standardized rate of change in muscle area was expressed as change in area/100 days. Univariate and multivariable analyses were performed to identify contributors to rate of muscle loss and survival. Results: Among 83 cirrhotics (NAFLD n = 26, ALD n = 39, VH n = 18), there were 20 (24.1%) deaths over 62.7 ± 41.3 months. The mean percentage change in psoas area was −0.03 ± 0.05/100d in controls and −3.52 ± 0.45/100d in cirrhosis ( P  < .001). The mean percentage change in psoas area was −1.72 ± 0.27/100d in NAFLD, −5.28 ± 0.86/100d in ALD and −2.29 ± 0.28/100d in VH. Among cirrhotics, patients with ALD had the lowest initial muscle area and most rapid rate of reduction in muscle area. Aetiology of liver disease, model for end‐stage liver disease (MELD) and the rate of loss of muscle area were independent risk factors for survival. Conclusions: Aetiology of liver disease is an independent risk factor for sarcopenia with the greatest rate of muscle loss noted in ALD. Survival in cirrhosis was dependent on initial muscle mass, rate of muscle loss and MELD score.